Dyspnoea and comorbidity contribute to anxiety and depression in interstitial lung disease. Issue 8 (12th August 2014) - Holland, Anne E.; Fiore, Julio F.; Bell, Emily C.; Goh, Nicole; Westall, Glen; Symons, Karen; Dowman, Leona; Glaspole, Ian
Abstract Background and objectives Little is known about the prevalence of anxiety in interstitial lung disease (ILD), and the contributors to depression are not clear. The aim of this study was to determine the prevalence and predictors of anxiety and depression in people with ILD. Methods One hundred and twenty‐four individuals with ILD (age 64 years (standard deviation 12), 48 idiopathic pulmonary fibrosis) participated. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale to determine likely cases and borderline cases. Associations with demographic data, respiratory function, 6‐min walk and Modified Medical Research Council Dyspnoea Scale (MMRC) were examined. Results The prevalence of anxiety was 31%, with clinically significant anxiety in 12%. Depression was present in 23% of individuals, with 7% having clinically significant depression. Independent predictors of anxiety were a higher MMRC score (P = 0.005, odds ratio (OR) for case 2.60, 95% confidence interval 1.37 to 4.92) and higher nadir SpO2 during walking (P = 0.003, OR for case 1.16, 1.04–1.30). Independent predictors of depression were a higher MMRC score (P = 0.006, case OR 3.84, 1.25–11.78, borderline case OR 2.44, 1.14–5.19) and a greater number of comorbidities (P = 0.003, case OR 2.02, 0.97–4.21, borderline case OR 2.26, 1.30–3.93). Conclusions Anxiety and depression are present in a significant minority of individuals with ILD. Dyspnoea and comorbidities are important contributors that may be amenable to intervention.